Measuring discrepancies between simple medullary and synchronous medullary/papillary thyroid carcinomas: a comparative cross-sectional study - Zhang, Daqi; Yang, Mingyu; Frattini, Francesco; Cestari, Andrea; Li, Kunlin; Wang, Hongbo; Chi, Hao; Sui, Chengqiu; Bai, Kecheng; Lan, Dongyuan; Dionigi, Gianlorenzo; Sun, Hui (Frontiers in Endocrinology, 2024)
OBJECTIVE: To study the clinicopathological characteristics of patients with synchronous medullary and papillary thyroid carcinomas. METHODS: The clinical data of patients with medullary thyroid carcinoma (MTC) operated in our hospital from February 2009 to February 2023 were evaluated using an analytical review approach. They were divided into an observation group (patients with synchronous MTC and papillary thyroid carcinoma PTC) and a control group (simple MTC) according to whether the clinical data were associated with MTC, in order to compare the clinical features, pathological types, stage characteristics and molecular biology characteristics of the two groups and to investigate the follow-up of the two groups. Results. The study included 122 MTC, 30 with synchronous MTC/PTC and 92 simple MTC. There was a significant difference between the groups when the MTC lesion diameter was ≤1cm in terms of preoperative CEA value (P＜0.05); when the MTC lesion diameter was ＞1cm, there was a statistical difference between the two groups in terms of preoperative Ctn value (P＜0.05). Type III was significantly different from the simple group, while type IV was more similar to the simple group. The preoperative serum Ctn value was positively correlated with maximum tumour diameter in both groups, although the correlation was stronger in the easy group. Preoperative Ctn and CEA were positively correlated with lymph node metastasis in the simple group, whereas there was no apparent correlation with lymph node metastasis in the combination group. The cut-off value of preoperative serum Ctn for cervical lymph node metastases in the simple group was 39.2pg/ml and for lateral cervical lymph node metastases 195.5pg/ml. The cut-off value of preoperative serum Ctn for cervical lymph node metastases in the combination group was 60.79pg/ml and for lateral cervical lymph node metastases 152.6pg/ml. Conclusion. In patients with synchronous medullary and papillary thyroid carcinomas, preoperative Ctn and CEA levels, calcifications, solitary lesions, combined goitre or thyroiditis differ significantly from simple MTC. Therefore, clinical management should pay attention to the above factors and early risk screening should be performed to improve prognosis as much as possible.